Issues in the Design of Growth Exercises. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
This paper deals with the design of quantitative exercises relating objectives for the growth of national income over the medium term to key macroeconomic policy variables. It focuses on the roles of capital formation, saving, and total factor productivity in the process of economic growth and examines the main conceptual and empirical problems involved in accounting for the growth of national income, dealing explicitly with the cost of borrowing from abroad. The paper examines the link, between fiscal and structural policies and the growth of productive capacity through the effect of those policies on productivity, saving and the cost of capital.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet